The WRKY Transcription Factor Family in Model Plants and Crops. (2nd November 2017) - Chen, Fei; Hu, Yue; Vannozzi, Alessandro; Wu, Kangcheng; Cai, Hanyang; Qin, Yuan; Mullis, Alison; Lin, Zhenguo; Zhang, Liangsheng
ABSTRACT: The WRKY gene family in flowering plants encodes a large group of transcription factors (TFs) that play essential roles in diverse stress responses, developmental, and physiological processes. In this review, we provided a comprehensive screenshot about the studies on WRKY TFs in model plants and in crops of economical relevance. Specifically, we discussed the history of discovery and functional characterization, classification, and evolutionary history, 3D structure and physiological functions of WRKY transcription factors. Based on the previous functional studies of WRKY genes in model plants such as Arabidopsis and rice, we summarized various roles of WRKY TFs in a broad range of biological processes as well as their degradation process. We also discussed the characterization and functional studies of WRKY TFs in important crops. Considering the rapid progress of high-throughput techniques, especially genomics and transcriptomics, which have been instrumental in advancing our understanding of the crop genomes, we comment one-by-one on the applications of a suite of new and high-throughput techniques to accelerate the studies of WRKY genes in crops.